PEMBERDAYAAN MASYARAKAT DESA TELOK SELONG ULU DALAM DETEKSI DINI HIPERTENSI - hammad, hammad; Ainun Sajidah; Rahmani; Rizkan Azhima; Rima Dewi; Nad’wa Huda (UPPM Poltekkes Kemenkes Banjarmasin, 2025)
Hypertension is one of the leading non-communicable diseases posing a serious public health threat in Indonesia, especially in South Kalimantan, which has the highest national prevalence. Telok Selong Ulu Village in Banjar Regency is among the areas with a significant number of hypertension cases. The lack of public knowledge and awareness about the signs and symptoms of hypertension, along with the limited skills of health cadres in conducting early detection, are major challenges. This community service program aimed to empower local health cadres and residents through education and training on hypertension and early detection techniques using medical devices. The activities included health education sessions, demonstrations of how to use digital blood pressure monitors, and checks for blood sugar, cholesterol, and uric acid levels. Results showed an increase in both knowledge and skills among participants in identifying hypertension independently. High enthusiasm was observed during hands-on practice, indicating the success of a participatory approach in promoting health awareness. It is hoped that the community will apply the acquired knowledge in daily life to prevent complications and reduce the prevalence of hypertension at the local level..